The experience of agri-food market regulation in the European Union under globalization - Vdovenko, Natalia; Shepelev, Vladimir (Technology audit and production reserves, 2015)
The paper examines the approaches to the agri-food market regulation in the EU using innovative, scientifically based resource allocation rules. The fundamental principles of the agri-food market regulation in the EU in the context of binding regulations, directives and decisions were investigated. It was concluded that the measures of regulation of the agri-food market, including domestic pork market, competitiveness support of domestic production need substantial revision. Therefore, an attempt to prove the feasibility of the agri-food market regulation, which is based on respect for the fundamental principles of food law with the established procedures, which should be consistent with the production standards of domestic and imported goods was made. The aforesaid will promote the application of experience of the EU member states in the area of agri-food market regulation by public application authorities, particularly in the issues of: a) regulation of speculative foreign competition, manifested through subsidized imports and dumped prices; b) acceleration of the implementation of the EU legislation in Ukraine; c) feasibility of dual agri-food market regulation as horizontal at the level of regulations and vertical at the level of directives.